The Influence of Product Quality, Product Design and Price on Vario Motorcycle Purchasing Decisions among Consumers in Lhokseumawe City - Aisa Putri Ariska; Rahmaniar Rahmaniar; Rusydi Abubakar; Heriyana Heriyana (Jurnal Intelek Insan Cendikia, 2025)
This research aims to determine the influence of product quality, product design and price on decisions about product quality, product design and purchase price for Vario motorbikes among consumers in Lhokseumawe City. The research method used is a quantitative method with multiple linear regression analysis techniques. The research results show that it significantly influences the decision to purchase a Vario motorbike. These findings show the importance of companies maintaining product quality, developing unique designs and setting appropriate prices in order to increase consumer buying interest, especially among the people of Lhokseumawe.